Efektivitas Pembelajaran Science Environment Technology and Society pada Materi Sistem Kardiovaskular di Tingkat Sarjana - Nuril Hidayati; Trio Ageng Prayitno (Universitas Nusantara PGRI Kediri, 2022)
The weakness of online learning in human anatomy and physiology courses is that the expected final ability cannot be achieved which has an impact on the quality of learning that is less and less than optimal output. There needs to be a learning process in which there is the use of integrated learning media, innovative learning approaches, one of which is the approach of science, environment, technology, and society. The purpose of this study was to determine the effect of learning SETS integrated with learning media on students' critical thinking skills. The research method used a quasi-experimental design with a pretest-posttest non-equivalent control group design. The results of the study showed that there was an effect of learning SETS integrated learning media on students' thinking skills with a significance value of anaova test of 0.00. The conclusion of this study is that there is a positive influence between the use of SETS learning integrated with learning media on students' critical thinking skills.